Association of IL-4 and IL-10 maternal haplotypes with immune responses to P. falciparum in mothers and newborns - Lokossou, Adjimon Gatien; Dechavanne, Célia; Bouraïma, Aziz; Courtin, David; Le Port, Agnès; Ladékpo, Rodolphe; Noukpo, Julien; Bonou, Désiré; Ahouangninou, Claude; Sabbagh, Audrey; Fayomi, Benjamin; Massougbodji, Achille; et al. (Springer, 2013)
Particular cytokine gene polymorphisms are involved in the regulation of the antibody production. The consequences of already described IL-4, IL-10 and IL-13 gene polymorphisms on biological parameters and antibody levels were investigated among 576 mothers at delivery and their newborns in the context of P. falciparum placental malaria infection. The study took place in the semi-rural area of Tori-Bossito, in south-west Benin, where malaria is meso-endemic. Six biallelic polymorphisms were determined by quantitative PCR using TaqMan® Pre-Designed SNP Genotyping Assays, in IL-4 (rs2243250, rs2070874), IL-10 (rs1800896, rs1800871, rs1800872) and IL-13 (rs1800925) genes. Antibody responses directed to P. falciparum MSP-1, MSP-2, MSP-3, GLURP-R0, GLURP-R2 and AMA-1 recombinant proteins were determined by ELISA. The maternal IL-4 −590 *T/IL-4 +33 *T haplotype (one or two copies) was associated with favorable maternal condition at delivery (high haemoglobin levels, absence of placental parasites) and one of its component, the IL-4 −590 TT genotype, was related to low IgG levels to MSP-1, MSP-2/3D7 and MSP-2/FC27. Inversely, the maternal IL-10 −1082 AA was positively associated with P. falciparum placenta infection at delivery. As a consequence, the IL-10 −819 *T allele (in CT and TT genotypes) as well as the IL-10 −1082 *A/IL-10 −819 *T/IL-10 −592 *A haplotype (one or two copies) in which it is included, were related to an increased risk for anaemia in newborns. The maternal IL-10 −1082 AA genotype was related to high IgG levels to MSP-2/3D7 and AMA-1 in mothers and newborns, respectively. The IL-13 gene polymorphism was only involved in the newborn's antibody response to AMA-1. These data revealed that IL-4 and IL-10 maternal gene polymorphisms are likely to play a role in the regulation of biological parameters in pregnant women at delivery (anaemia, P. falciparum placenta infection) and in newborns (anaemia). Moreover, IL-4, IL-10 and IL-13 maternal gene polymorphisms were related to IgG responses to MSP-1, MSP-2/3D7 and MSP-2/FC27 in mothers as well as to AMA-1 in newborns.